2014
DOI: 10.1016/j.dyepig.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Zn(II)-bisthienylethynylbipyridine complex: Preparation, characterization and vapochromic behaviour in polymer films

Abstract: In the present work, we report the vapochromic behaviour of PMMA films doped with small amounts of 1a:Zn fluorophore, a Zn 2+ adduct of the bisthienylethynylbipyridine ligand. 1a:Zn exhibited polarity-dependent changes in the fluorescence spectral properties when dissolved in solvents with different polarity index, indicating that its fluorescence states are of intramolecular charge transfer character. When 1a:Zn was dispersed in the PMMA matrix, its emission resulted barely influenced by the polymer environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The emission intensity dropped by about 80% after 8 s of exposure. This extremely sensitive solvent dependence, never achieved previously by our research group [ 22 , 24 , 25 , 28 , 40 ], agrees well with the characteristics of JCBF. Notably, the progressive VOC adsorption and successive absorption by the polymer matrix triggers the reorganization energy of the JCBF excited transition state from the LE to the non-emissive TICT.…”
Section: Resultssupporting
confidence: 90%
“…The emission intensity dropped by about 80% after 8 s of exposure. This extremely sensitive solvent dependence, never achieved previously by our research group [ 22 , 24 , 25 , 28 , 40 ], agrees well with the characteristics of JCBF. Notably, the progressive VOC adsorption and successive absorption by the polymer matrix triggers the reorganization energy of the JCBF excited transition state from the LE to the non-emissive TICT.…”
Section: Resultssupporting
confidence: 90%
“…Another contribution of organometallic fluorophores was recently demonstrated by Platonova et al who reported the vapochromic behaviour of PMMA films doped with small amounts of a Zn adduct of the bisthienylethynylbipyridine ligand . The Zn(II) complex exhibited polarity‐dependent changes in fluorescence spectral properties when dissolved in solvents with different polarity index, indicating that its fluorescence states are of intramolecular charge transfer (ICT) character (Fig.…”
Section: Fluorescent Vapochromic Materials From Fluorophore − Polymermentioning
confidence: 87%
“…Emerging strategies for the colorimetric and specific detection of VOCs are based on fluorophores embedded in plastic materials or in fluorescent conjugated polymers . Notable is the fact that the optical behaviour of these polymer‐based VOC sensors is tunable by specific interactions between the polymer matrix and the fluorophore units.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pressing issues in global security are triggering the design of novel chromogenic compounds aimed at detecting environment changes with optical responses even more effective. For example, thermoplastic indicators containing fluorophore sensitive to viscosity changes have been used with success for the detection of VOCs . Notably, plastic films containing moderate amounts of the chromophoric probe (<0.1 wt%) display fluorescence variations upon the exposure to well‐interacting VOCs due to an induced plasticization of the continuous polymer phase .…”
Section: Introductionmentioning
confidence: 99%
“…For example, thermoplastic indicators containing fluorophore sensitive to viscosity changes have been used with success for the detection of VOCs. [3][4][5][6][7][8][9][10][11][12] Notably, plastic films containing moderate amounts of the chromophoric probe (<0.1 wt%) display fluorescence variations upon the exposure to well-interacting VOCs due to an induced plasticization of the continuous polymer phase. [3][4][5][6]9,13 Plasticization means also viscosity decreasing, thus allowing the dispersed fluorophores to aggregate together upon a certain concentration threshold, which in turn causes evident color changes.…”
mentioning
confidence: 99%